Automated Library Data Tracking System By Smartphone - Khan, AP; Patil, YB; Patil, PR; Nagarale, MS; Patil, RV (International Journal of Computer Sciences and Engineering, 2025)
Automated Library data tracking system by smartphone is the android based application containing the facility for the student and the staff of the library to track and transact the book and library system. These application has the functionality to register the student on the library database according the branch and enrolment number. In this system the student can make the book issue and return easily by using the QR code. Each and every student has the unique QR code instead of paper ID card. The book also has the QR code by scanning these QR codes the librarian can issue or return the book. Application also has the facility for student to search for the book availability and college department information with teacher information. The staff can also use the application to track the book data and make the entry for new books to the library. And can also make the entry for the college department staff. All the information about the staff, student and book transaction is stored and managed by the centralized database over the internet. All the system is fully online. The website middle ware is also designed to handle and manage all request by the staff, student and book by the admin.